SOME ASPECTS OF TOURISM DEVELOPMENT IN UZBEKISTAN (Scientific journal of the Fergana State University, 2024)
The article describes the reforms implemented in the field of tourism in Uzbekistan, the role of tourism in increasing the standard of living and employment of the population, and the recreational opportunities of geographical objects. The importance of tourism in the gross domestic product of some countries was also considered. Some recommendations on the development of the tourism sector in Uzbekistan were given.